Voláteis induzidos por herbivoria em plantas de mandioca e atratividade a ácaros (Acari: Tetranychidae: Phytoseiidae) - Bezerra, Ranna Heidy Santos (2017)
Under natural conditions, plants release volatile organic compounds (VOCs) that can differ either qualitative or quantitatively from those induced by herbivory. Induced VOCs are specific, varying with the attacked plant species, with the herbivore, and the developmental stages and conditions from both species. Induced VOCs mediate important ecological interactions. They can attract predators and parasitoids, repel herbivores and mediate communication between neighboring plants and different parts of the same plant. Cassava (Manihot esculenta) is a native plant from Brazil cultivated in all regions, but mainly in the northeast region. It has an important role in animal and human feeding, manufacturing of industrial products and the creation of jobs and income. Several studies have been conducted to identify the volatile compounds induced by herbivory and observe their influence in the behavior of herbivores and their natural enemies, however, to date little is known about the VOCs emissions of cassava plants and their role in arthropod-plant interactions. This study aimed at identifying the volatiles induced by herbivory from the herbivorous mites Mononychellus tanjoa, Tetranychus urticae and T. gloveri in cassava plants, and how these herbivorous mites and the predatory mite Neoseiulus idaeus respond to induced VOCs blends. Twenty three compounds (monoterpenes, sesqueterpenes, aldehyde, alcohol, esters, oxime, phenylpropanoid and indole) were identified in the headspace of healthy and mite-damaged cassava plants. Herbivore-damaged plants released novel compounds that weren’t emitted by the healthy plants. Significant difference were found in the emission of methyl salicylate by M. tanajoa and T. gloveri infested plants, and (Z)-3-hexen-1-ol infested with T. urticae, when compared to healthy plants. The compounds (Z)-β-ocimene, 2-methyl propanol oxime, 2-methyl butanoloxime, indole, methyl anthranilate and (E)-nerolidol were only induced by herbivory from T. urticae, and may be involved in the attraction of N. idaeus, since the predator with experience in cassava significantly preferred plants infested with T. urticae compared to healthy plants. Tetranychus gloveri with cassava experience preferred healthy cassava plants compared to clean air, demonstrating that the plant produces volatiles that are attractive to herbivores. It can be concluded that after the herbivory cassava plants emit VOCs that differ qualitatively and quantitatively from those released by healthy plants and the total amount emitted increases with the density of mites in the plant. Despite the emission of VOCs known to attract predatory mites by plants infested with M. tanajoa and T. gloveri, N. idaeus did not prefer infested plants, suggesting that the level of induction was not sufficient or these herbivorous mites are not attractive to the predator.